THE ROLE OF INDEPENDENT WORK FOR STUDENTS IN EDUCATIONAL PROCESS - Sanakulova, Aziza (Журнал иностранных языков и лингвистики, 2021)
In this article is analyzed role of the independent work student in educational process. Since, independence form of necessity-motivation sphere, mental, physical and morally volitional efforts of students.